The dynamic competition between item distinctiveness and attentional boost effect. - Meng, Yingfang; Chen, Peijie; Xu, Shuangxing; Zhao, Xin; Huang, Qiuhua; Paterson, Kevin B. (Memory & Cognition, 2026)
The Attentional Boost Effect (ABE) refers to the enhancement in memory for background information that co-occurs with the detection of a target in a detection task. Previous research suggests that this effect is modulated by item distinctiveness, meaning that when background items have high distinctiveness (e.g., low-frequency words, negative items), the ABE is significantly reduced or even disappears. However, in previous studies, the detection stimulus and background items were synchronized in their onset times, which could lead to maximal overlap between the two enhancement effects. Accordingly, to further understand the relationship between item distinctiveness and target detection, we manipulated distinctive and nondistinctive memory items in three experiments and manipulated the onset time of detections stimuli. Distinctiveness was varied by manipulating the word frequency (Experiment 1), and the emotional valence of both words (Experiment 2) and images (Experiment 3). The detection stimulus was presented within two time windows: 0–100 ms or 400–500 ms during the presentation of background items. The results indicated that, compared with word frequency, negative valence exerted a more pronounced modulation of the ABE, and this modulation was not influenced by the onset time of detection stimulus. This finding further deepens our understanding of the interaction between item distinctiveness and the ABE, suggesting a complex competitive relationship between the two effects.